Induction of anterior gradient 2 (AGR2) plays a key role in insulin-like growth factor-1 (IGF-1)-induced breast cancer cell proliferation and migration - Li, Zheqi (Med Oncol, 2015)
Anterior gradient 2 (AGR2) is a promising anti-tumor target associated with estrogen receptor expression and metastatic progression of breast cancer. Insulin-like growth factor-1 (IGF-1) is another potent factor that stimulates breast cancer progression and mediates anti-estrogen drug resistance. However, the precise mechanism and connections between these two factors in breast cancer drug resistance have not been fully elucidated. Here, for the first time, we decipher that IGF-1 remarkably induces AGR2 in the MCF7 cell line, through an estrogen response element (ERE) between −802 and −808 bp and a leucine zipper transcription factor-binding site located between −972 and −982 bp on the AGR2 promoter. We also found that the ERK1/2 and AKT pathways mediate estrogen receptor-α at the upstream of ERE and that the JNK pathway activates the leucine zipper site through the c-Jun/c-Fos complex. Additionally, our data suggest that knockdown of AGR2 reduces IGF-1-induced cell proliferation, migration and cell cycle progression. Therefore, we report that AGR2 is a key modulator involved in IGF-1-induced breast cancer development. We propose that the identification of the mechanism linking the IGF-1/insulin signal and AGR2 promoter activation is important, because it provides insights into the development of anti-breast cancer drugs.